DISTORSI PASAR DALAM PERSPEKTIF ISLAM - Miftahurrazak, Muhammad; Rahman, Arif; Albahi, Muhammad (Politeknik Bisnis Indonesia, 2024)
Market dynamics in the modern economic system often experience various deviations that harm the interests of the wider community. This article examines the phenomenon of market distortions from an Islamic economic perspective using a qualitative-descriptive research method. The research aims to identify forms of market distortions, causal factors, and solutions offered within the framework of Islamic economics. Through literature analysis and conceptual understanding, this study found that market distortions can occur in various forms such as monopoly, asymmetric information, and unfair intervention. The causative factors include weak regulation, low moral awareness, and an unjust economic structure. The Islamic perspective offers a comprehensive solution through the principle of justice (al-'adl), transparency of transactions, and ethics-based supervisory mechanisms. This article makes a theoretical contribution in understanding market distortions from the perspective of Islamic economics and offers a conceptual framework to realize a fair market.